FEATURES OF THE SOCIAL DEVELOPMENT OF THE COUNTRIES OF SOUTHEAST ASIA (ON THE EXAMPLE OF MALAYSIA) - Tunis Khojiev (Modern American Journals, 2025)
This study examines the first stage of Malaysia’s modernization process (1957-1990s), highlighting its historical, socio-economic, and political dimensions. Following independence from British colonial rule in 1957, Malaysia confronted the dual challenge of overcoming the colonial legacy—characterized by a raw material- and agriculture-based economy—and laying the foundation for a diversified, modern economic system.
Keywords: Modernization, Rukunegara, the bumiputera, NEP, TNK, a five-year economic plan, import goods, export diversification.